Acceptable Risk - Cook, Robin (London Pan Books, 1996)
From the doctor whose bestselling thrillers have created fear and excitement for over a decade comes a harrowing tale of ambition, abandoned ethics and uncontrollable greed.
Keywords: Medicine--Research -- Designer drugs -- American fiction